Probabilitas dalam Finite State Machine Agen Cerdas Edugame “Ajut-Ajut Kids” - Siti Lailiyah; Yunita Yunita; Syamsuddin Mallala (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Educational game “Ajut-ajut Kids” is developed in multimedia stages to introduce the Dayak Benuaq language for children. In this matching game, players must match two or more images and words in Dayak language. This study applies randomization to shuffle position of images and words in each round. It makes the game more challenging. Random and probability in-game agents are also applied, which will accompany children to play the kid character in Dayak clothes. Game agents, which apply the Finite State Machine (FSM) model, will provide expressions like pleasure, sadness, etc., according to the child's playing style. Random implementation and credibility in the FSM model allows agents to give random expressions. This makes the agent more natural. The result of this study proves randomization and probability have succeeded make this game more interesting and interactive to children.